A COMPARISON OF EGFR USING SERUM CREATININE AND CYSTATIN FOR THE ASSESSMENT OF RENAL INVOLVEMENT IN HYPERTENSION. - JITHESH TK,; RIJU MATHEW,; JAYAPAL. V,; VIJAYAKUMAR. T, (International Journal of Pharma and Bio Sciences, 2013)
A study was conducted to evaluate the usefulness of GFR to assess the renal involvement in hypertension. GFR was assessed using the conventional blood urea and serum creatinine values and the eGFR is calculated based on serum creatinine by using the MDRD formula and Cockcroft – Gault formula. The values obtained were compared with serum Cystatin C and Cystatin based eGFR. It was observed that even though serum creatinine based eGFR is a good marker for renal assessment this method is lacks sensitivity and cannot be applied in GFR blind area. Cystatin C , Cystatin C based eGFR were found to be more reliable and sensitive than the earlier markers particularly in areas were the decrease in GFR is marginal. Hence it is suggested that Cystatin C and Cystatin C based eGFR are better markers for the assessment of renal involvement in hypertension.